A Lean Approach to Self‐Discovery and Social Innovation. (7th February 2023) - Hopson, Jordan
Abstract : You might be saying, "Hold on, I don't even know what I'm passionate about." If you're looking to create positive change, see how the lean process can enable your journey of self‐discovery. Start small, and Build, Measure, and Learn!